2019
DOI: 10.1080/14786419.2019.1578763
|View full text |Cite
|
Sign up to set email alerts
|

New p-terphenyl and benzoquinone metabolites from the bioluminescent mushroom Neonothopanus nambi

Abstract: Two new p-terphenyls, neonambiterphenyls A and B (1-2), a new benzoquinone, neonambiquinone A (3), together with six known sesquiterpenes (4-9), were isolated from the bioluminescent mushroom Neonothopanus nambi PW3. The isolated compounds were identified by mass, IR and spectroscopic analyses (1D and 2D NMR). Compounds 1-3 and 5-7 showed cytotoxicity against cancer cell lines, KB, NCI-H187 and MCF-7 with IC 50 values ranging from 1.45 to 49.31 µg/mL. In addition, compounds 1 and 5 showed cytotoxicity against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The structural diversity of the natural p-terphenyls mainly resulted from the variation of the ring B, the number and the position of hydroxy groups, and the changes of the phenol to quinone functions. Approximately 230 natural p-terphenyls have been identified from the year 1877 to 2018 (Li et al 2018;Liu 2006), and this number is growing every year (Kalansuriya et al 2019;Kalvo et al 2018;Lin et al 2019;Lu et al 2019;Narmani et al 2019;Ren et al 2018;Sangsopha et al 2019;Song et al 2019;Wang et al 2019b;Xu et al 2018). Our present work isolated and identified a new p-terphenyl alcohol with a dibenzofuran moiety from the marine sponge-derived fungus A. candidus OUCMDZ-1051, as well as nine known p-terphenyl alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…The structural diversity of the natural p-terphenyls mainly resulted from the variation of the ring B, the number and the position of hydroxy groups, and the changes of the phenol to quinone functions. Approximately 230 natural p-terphenyls have been identified from the year 1877 to 2018 (Li et al 2018;Liu 2006), and this number is growing every year (Kalansuriya et al 2019;Kalvo et al 2018;Lin et al 2019;Lu et al 2019;Narmani et al 2019;Ren et al 2018;Sangsopha et al 2019;Song et al 2019;Wang et al 2019b;Xu et al 2018). Our present work isolated and identified a new p-terphenyl alcohol with a dibenzofuran moiety from the marine sponge-derived fungus A. candidus OUCMDZ-1051, as well as nine known p-terphenyl alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the NMR data of 2 were very similar those of nambiscalarane (8), with slight differences arising from the substitution of the hydroxy group at C-11 by a malonate. NOESY correlations (Figure 3) between H-11β/H 3 -21/H 3 -22/H 3 -23 and H-6β/H-7β/H 3 -19/H 3 -21/H 3 -22, as well as the large 1 H-1 H coupling constants between H-6/H-7 (11.2 Hz) and H-11/H-12 (11.2 Hz) indicated that the relative configuration of compound 2 was identical to that of compound 1. The absolute configuration of compound 2 was established through comparison of calculated and experimental ECD curves.…”
Section: Structural Characterization Of the New Compoundsmentioning
confidence: 97%
“…The luminescent mushroom Neonothopanus nambi belongs to the Omphalotaceae family. It is known as 'Hed Ruang Sang Sirin-ratsami' or 'Sirin-ratsami mushroom' in Thai [1]. Previous agricultural studies have shown that N. nambi can induce systemic resistance against root-knot nematodes such as Meloidogyne incognita in tomato plants [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites isolated from species of the genus Aspergillus have continually attracted the interest of pharmacologists due to their broad array of biological activities and their structural diversity (Wang et al, 2017). p-Terphenyl derivatives have been reported with diverse biological activities, such as neuraminidase inhibitory (Guo et al, 2012), α-glucosidase inhibitory (Zhang et al, 2018), antioxidant (Yen et al, 2001, cytotoxic (Cai et al, 2011;Sangsopha et al, 2019;Yurchenko et al, 2017), antibacterial (Yan et al, 2017, and immunosuppressive activities (Ivanets et al, 2018).…”
Section: Introductionmentioning
confidence: 99%